Effects of different batches of Neoparamoeba perurans and fish stocking densities on the severity of amoebic gill disease in experimental infection of Atlantic salmon, Salmo salar L - Crosbie, PBB; Bridle, AR; Leef, MJ; Nowak, BF (Aquaculture Research, 2010)
Currently, there are two methods of inducing laboratory-based amoebic gill disease (AGD) in Atlantic salmon, Salmo salar L.: cohabitation with infected fish or exposure to a suspension of amoebae. Amoebic gill disease cannot be induced with cultured amoebae; therefore, the only source of the infective organism is salmon with the disease. For experimental purposes and to maintain pathogen supply, salmon are kept in an infection tank and amoebae are isolated from salmon once the disease establishes. In this way, discrete batches of amoebae are collected periodically. This study investigated the infective ability of different batches of amoebae. Furthermore, the effect of stocking density of salmon on the progression of AGD was also examined. The infective ability of different batches of amoebae isolated periodically from AGD-affected salmon varied in terms of quantifiable pathology. Salmon stocking density had a significant impact on survival after amoebae challenge, with morbidity beginning 23 days post challenge in tanks stocked at 5.0 kg m -3 and 29 days for those stocked at 1.7 kg m -3. For uniform initiation of AGD in multiple tanks, amoebae batches should be equally divided and added to tanks until the required concentration is reached and to maintain a standard biomass between replicate tanks and treatments. 2010 The Authors. Aquaculture Research 2010 Blackwell Publishing Ltd.